Development of a material efficiency strategy selection model for electrical and electronic manufacturing industry / Ho Fu Haw - Ho , Fu Haw (2018)
The objective of this study is to examine the link between organizational change factors and the selection of appropriate material efficiency strategies for manufacturers in Malaysia, specifically in the electrical and electronics (E&E) industry. There are various change factors that can influence the implementation of material efficiency strategies in manufacturing companies and these factors are often interrelated. These factors vary depending on the country and manufacturing sector, which are affected by the fluctuating market conditions. Thus, the implementation of material efficiency strategies is a rather arduous task, particularly in selecting an appropriate strategy among the various material efficiency strategies available. A mixed-method approach (qualitative and quantitative) was chosen for this study in order to collect and analyse the data obtained from selected E&E companies in Malaysia. Semi-structured interviews were conducted to explore material efficiency strategies and change factors in these E&E companies. The Analytic Hierarchy Process (AHP) approach was used to prioritize the change factors and link them with each material efficiency strategy. Two main material efficiency areas were identified: (a) material efficiency strategies and (b) organizational change factors (drivers, barriers and enablers). The association and proposition links of the material efficiency strategies and its change factors were built and presented in the form of a material efficiency strategy decision model. In addition, a decision support tool is constructed to select the suitable material efficiency strategies. In this study, the organizational change factors and material efficiency strategies were linked by establishing a comprehensive integrated decision model to prioritize the selection of material efficiency strategies. The decision propositions links were established for each change factor and each material efficiency strategy. This is a significant contribution to knowledge since it takes into account analytical decision perspectives in the selection of material efficiency strategies. In addition, the inclusion of multiple change factors provides a new theoretical perspective on the implementation of material efficiency strategies. The decision support tool developed in this study can be used in practical applications, particularly to assist practitioners in making appropriate decisions in prioritizing the selection of material efficiency strategies.